2012
DOI: 10.12659/msm.883603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPAP treatment on endothelial function and plasma CRP levels in patients with sleep apnea

Abstract: SummaryBackgroundContinuous positive airway pressure (CPAP) is the most effective method for treating obstructive sleep apnea syndrome (OSAS) and alleviating symptoms. Improved sleep quality with effective CPAP therapy might also contribute to attenuated systemic inflammation and improved endothelial function, with subsequent reduction of cardiovascular risk.The aim of this study was to assess the effect of 3-month CPAP therapy on brachial artery flow-mediated dilation (FMD) and plasma C-reactive protein (CRP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
2
26
0
4
Order By: Relevance
“…Thus, it is challenging to integrate our findings with the existing literature. Several studies suggest that FMD may be reduced among groups with disrupted sleep, such as adults doing night shift work and patients with confirmed OSA and (Amir et al,2004;Patt et al,2010), with other work reporting that patients with OSA who were treated with continuous positive airway pressure (CPAP) showed increased FMD (Panoutsopoulos et al,2012). The current study extends those findings by finding associations between sleep quality and FMD among non-shift working adults sampled from the general population, who did not have a previously diagnosed sleep disorder.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, it is challenging to integrate our findings with the existing literature. Several studies suggest that FMD may be reduced among groups with disrupted sleep, such as adults doing night shift work and patients with confirmed OSA and (Amir et al,2004;Patt et al,2010), with other work reporting that patients with OSA who were treated with continuous positive airway pressure (CPAP) showed increased FMD (Panoutsopoulos et al,2012). The current study extends those findings by finding associations between sleep quality and FMD among non-shift working adults sampled from the general population, who did not have a previously diagnosed sleep disorder.…”
Section: Discussionsupporting
confidence: 75%
“…Our group and others have shown a gradual decrease of CRP levels with effective PAP therapy, which could subsequently improve cardiovascular morbidity associated with OSAS [19,[65][66][67][68][69] , whereas others found that PAP therapy did not significant change CRP levels, regardless of PAP therapy duration [39,42,65,[70][71][72][73][74] . Furthermore our study [60] showed that after PAP therapy CRP was decreased more slowly in females compared to matched for OSAS severity males.…”
Section: Effect Of Positive Airway Pressure Therapy On Levels Of Crpmentioning
confidence: 65%
“…38 The beneficial effect of CPAP on endothelial dysfunction in subjects with OSA partially stems from reductions in oxidative and inflammatory activities, as well as improvements in both endothelial repair capacity and nitric oxide bioavailability. [10][11][12][13][14][15][16][17][18][19][20] The subgroup analysis showed that with respect to improved FMD, a longer duration of CPAP was no better than a shorter duration (2.49% vs 3.73%). After 1 week, CPAP significantly changed the FMD of subjects with OSA compared with the baseline level, from 3.3 Ϯ 0.3% Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also explored the effects of CPAP on FMD as a surrogate vascular outcome. [10][11][12][13][14][15][16][17][18][19][20] Although these studies demonstrated the favorable effect of CPAP on endothelial function, confounding factors such as obesity, insulin resistance, and metabolic syndrome, all of which influence endothelial function, must also be taken into account. In this review, we sought to retrieve all published studies on the effects of CPAP on FMD and NMD in subjects with OSA and to quantify the potential contribution of CPAP to improving endothelial function.…”
Section: Introductionmentioning
confidence: 99%